Effect of Castration Type and Diet on Growth Performance, Serum Sex Hormones and Metabolites, and Carcass Quality of Heavy Male Pigs - Leticia Pérez-Ciria; Francisco Javier Miana-Mena; Javier Álvarez-Rodríguez; Maria Angeles Latorre (Animals, 2022)
A trial was carried out to study the effect of type of castration and diet on pigs destined for Teruel ham production, which is a Spanish protected designation of origin for dry-cured ham. A total of 144 Duroc × (Landrace × Large White) male pigs were used. Half of them were surgically castrated and the other half were immunocastrated with three doses at approximately 25, 58 and 79 kg of body weight. Furthermore, three diets (control vs. high energy vs. low crude protein-CP- and amino acids-AA) were tested from 80 to 137 kg of body weight. Growth performance, serum sex hormones and metabolites, and carcass quality were evaluated. Immunocastrated males grew faster and had better feed conversion ratio than surgically castrated males, but presented lower carcass fatness. Pigs fed the high-energy diet and the low-CP and -AA diet were more efficient at transforming feed into gain than those fed the control diet, but no effect was detected on carcass quality. In conclusion, surgically castrated males are preferable than immunocastrated males for Teruel dry-cured ham elaboration. Besides, a high-energy diet or a low-CP and -AA diet might improve productive performances, but does not provide any benefit in terms of carcass quality.